Pola Pendidikan Humanis Religius pada Rumah Pintar âPijoenganâ Bantul Yogyakarta - Munjahid, Munjahid; Kuswanto, Heri (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
The academic anxiety in this paper is the number of educational processes deviating from its primary mission of humanizing humans. The learning process focuses only on try out and discussion of exam questions while the formation of attitudes and skills is ignored. The formulation of the problem in this article is: What is the pattern of religious humanist education in Rumah Pintar "Pijoengan" Bantul Yogyakarta? What is the implication of humanist education in Rumah Pintar "Pijoengan" Bantul Yogyakarta? How are the supporting and inhibiting factors of the implementation of religious humanist education in Smart House "Pijoengan" Bantul Yogyakarta ?. The results of his research are: Humanist education pattern that is widely implemented is "Development of personality and soul of the subjects of education", "Social sensitivity" and "Expansion of Consciousness". Implications: increased insight, prosperity, independence, health, religious awareness, humanist attitudes, community soft skills and the availability of trained workers. Supporting factors: government political support, managerial mentality, natural factors, managerial ability to work together, awareness of educational institutions. Inhibiting factors: decreasing the number of donors, tool functions, facilities and infrastructure, limited types and number of facilities, educators and education, marketing, the number of hamlets that are difficult to reach.Â Ø¥Ù Ø§ÙÙØ¶ÙØ© Ø§ÙÙØ¨ØÙØ«Ø© ÙÙ ÙØ°Ø§ Ø§ÙÙÙØ§Ù ÙÙ ÙØ«Ø±Ø© Ø¹ÙÙÙØ§Øª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¹Ø§Ø¯ÙØ© Ø¹Ù Ø±Ø³Ø§ÙØªÙØ§ Ø§ÙØ£Ø³Ø§Ø³ÙØ© ÙÙ Ø£ÙØ³ÙØ© Ø§ÙØ¨Ø´Ø±. ØªÙØªØµØ± Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙ Ø¹ÙÙ Ø§ÙØªØ±ÙÙØ² ÙÙ Ø§ÙØ¥Ø¹Ø¯Ø§Ø¯ ÙÙÙØ§Ø¨ÙØ© Ø§ÙØ§ÙØªØØ§ÙØ§Øª ÙØ§ÙØªØ¯Ø±ÙØ¨ Ø¹ÙÙ Ø¥Ø¬Ø§Ø¨Ø© Ø§ÙØ£Ø³Ø¦ÙØ©Ø ÙØ£ÙØ§ Ø¬Ø§ÙØ¨ ØªÙÙÙÙ Ø§ÙØ´Ø®ØµÙØ© ÙØ§ÙÙÙØ§Ø¡Ø© ÙÙÙÙÙÙ. ÙØ£Ø³Ø¦ÙØ© Ø§ÙØ¨ØØ« ÙÙ ÙØ°Ø§ Ø§ÙÙÙØ§Ù ÙÙ : ÙØ§ ÙÙ ÙÙØ· Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ³Ø§ÙÙØ© Ø§ÙØ¯ÙÙÙØ© ÙÙ ÙØ±ÙØ² Ø§ÙØªØ¹ÙÙÙ " âPijoenganâ Ø¨Ø§ÙØªÙÙ ÙÙØºÙØ§ÙØ±ØªØ§ ØØ ÙÙØ§ Ø£Ø«Ø± ÙÙØ· Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ³Ø§ÙÙØ© Ø§ÙØ¯ÙÙÙØ© ÙÙ ÙØ±ÙØ² Ø§ÙØªØ¹ÙÙÙ " âPijoenganâ Ø¨Ø§ÙØªÙÙ ÙÙØºÙØ§ÙØ±ØªØ§ ØØ ÙÙØ§ Ø§ÙØ¹ÙØ§ØµØ± Ø§ÙØ¯Ø§Ø¹ÙØ© ÙØ§ÙØ¹Ø§Ø¦ÙØ© ÙØ¹ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ³Ø§ÙÙØ© Ø§ÙØ¯ÙÙÙØ© ÙÙ ÙØ±ÙØ² Ø§ÙØªØ¹ÙÙÙ " âPijoenganâ Ø¨Ø§ÙØªÙÙ ÙÙØºÙØ§ÙØ±ØªØ§ Ø. ÙÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« ÙÙ : Ø¥Ù ÙÙØ· Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ³Ø§ÙÙØ© Ø§ÙÙØ·Ø¨ÙØ© ÙØ«ÙØ±Ø§ ÙÙ "ØªÙÙÙØ© Ø´Ø®ØµÙØ© Ù ÙÙØ³ÙØ© Ø§ÙØ·Ø§ÙØ¨Ø ÙØ§ÙØØ³ÙØ§Ø³Ø© Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ©Ø ÙØªÙØ³ÙØ¹ Ø§ÙÙØ¹Ù. Ø£ÙØ§ Ø§ÙØ¢Ø«Ø§Ø± ÙÙÙØ§ ÙÙ Ø§Ø±ØªÙØ§Ø¡ Ø£ÙÙ Ø§ÙÙØ¹Ø§Ø±ÙØ ÙØ§ÙØ±ÙØ§ÙÙØ©Ø ÙØ§ÙØ§Ø¹ØªÙØ§Ø¯ Ø¹ÙÙ Ø§ÙÙÙØ³Ø ÙØ§ÙØµØØ©Ø ÙØ§ÙÙØ¹Ù Ø¨Ø§ÙØªÙÙÙØ¹Ø ÙØ§ÙÙÙÙÙ Ø§ÙØ¥ÙØ³Ø§ÙÙØ ÙØ§ÙÙÙØ§Ø±Ø§Øª Ø§ÙÙØ§Ø¹ÙØ© ÙÙÙØ¬ØªÙØ¹ ÙØªÙÙÙØ± Ø§ÙØ¹ÙÙØ§Ù Ø§ÙÙØªØ¯Ø±ÙØ¨ÙÙ. Ø£ÙØ§ Ø§ÙØ¹ÙØ§ØµØ± Ø§ÙØ¯Ø§Ø¹ÙØ© ÙÙÙ : Ø§ÙØ¯Ø§Ø¹Ù Ø§ÙØ³ÙØ§ÙÙ ÙÙ Ø§ÙØÙÙÙØ©Ø ÙØ´Ø®ØµÙØ§Øª Ø§ÙÙØ³Ø¤ÙÙÙÙØ ÙØ§ÙØ¹ÙØµØ± Ø§ÙØ·Ø¨ÙØ¹Ù. Ø£ÙØ§ Ø§ÙØ¹Ø§ÙØ§ØµØ± Ø§ÙØ¹Ø§Ø¦ÙØ© ÙÙÙ : Ø§ÙØ®ÙØ§Ø¶ Ø§ÙÙØªØ¨Ø±Ø¹ÙÙØ ÙÙØ§Ø¦Ø¯ Ø§ÙØ£Ø¬ÙØ²Ø©Ø Ø§ÙÙØ±Ø§ÙÙ ÙØ§ÙÙØ³Ø§Ø¦ÙØ ÙÙÙØ© ÙÙÙØ© ÙÙÙØ¹ÙØ© Ø§ÙÙØ±Ø§ÙÙ ÙØ§ÙÙØ³Ø§Ø¦ÙØ ÙØ§ÙÙØ¯Ø±Ø³ÙÙ ÙØ§ÙÙÙØ¸ÙÙÙ Ø§ÙØªØ±Ø¨ÙÙÙÙØ ÙØ§ÙØªØ³ÙÙÙØ ÙÙØ«Ø±Ø© Ø§ÙÙØ±Ù Ø§ÙØµØ¹Ø¨Ø© Ø§ÙÙØµÙÙ Ø¥ÙÙÙØ§.